Photopicking: In Situ Approach for Site‐Specific Attachment of Single Multiprotein Nanoparticles to Atomic Force Microscopy Tips. (13th January 2017) - Liashkovich, Ivan; Rosso, Gonzalo; Rangl, Martina; Ebner, Andreas; Hafezi, Wali; Kühn, Joachim; Schön, Peter; Hinterdorfer, Peter; Shahin, Victor
Abstract : Ligand–receptor interactions are fundamental in life sciences and include hormone–receptor, protein–protein, pathogen–host, and cell–cell interactions, among others. Atomic force microscopy (AFM) proved to be invaluable for scrutinizing ligand–receptor interactions at the single molecular level. Basically, a ligand is attached to the AFM tip while its cognate receptor is immobilized on a surface or vice versa, and interactions are studied following triggered ligand–receptor binding. However, with rising biological complexity it becomes increasingly challenging to attach a single intact biomolecule to the tip and ensure interaction‐specific orientation. This study presents a novel strategy of inducible in situ tip functionalization with complex multiprotein nanoparticles exemplified by viral capsids, termed photopicking. It ensures a firm attachment of single 125 nm large capsids to the tip. Specific orientation is attained by weak immunosorption of capsids to the substrate and strong photoinducible covalent cross‐linking to the tip. Validation of the tip functionalization success is immediate in situ. The versatility of the strategy is further demonstrated on 20–60 nm large amino‐modified nanoparticles. In conclusion, considering the size range of the tested biomolecules, the presented strategy is applicable to viruses, viral particles, cellular organelles, multiprotein ligands/receptors, and therapeutic nanoparticles, among others. It therefore opens up exciting new avenues in broad biomedical research fields. Abstract : A schematic of the photopicking approach to pick up a single multiprotein nanoparticle is given, exemplified by a viral capsid with a site‐specific orientation.